Use aging-resistant porcelain insulators in low temperature environments

Through the preparation method of modified titanium dioxide powder, a ceramic insulator material that is resistant to aging was prepared, which solves the problem of broken accidents in low-temperature environments, improves the strength of the material and the resistance to freeze-thaw aging, and expands the scope of use.

CN117550885BActive Publication Date: 2025-03-11JIANGXI PINGXIANG EAST CHINA EXPORT ELECTRIC PORCELAIN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311494789.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2025-03-11
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

Porcelain insulators are prone to fracture accidents in low temperature environments, affecting the safe and stable operation of the power system.

Method used

Using the preparation method of modified titanium dioxide powder, aging-resistant porcelain insulator material is prepared through specific chemical reactions and treatment steps. The raw materials of this material include mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin clay.

Benefits of technology

It improves the strength and freeze-thaw aging resistance of porcelain insulators, making them less likely to cause low-temperature cracking and damage in environments with large temperature changes and low-temperature areas, and expands the scope of use of porcelain insulators.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an aging-resistant porcelain insulator for use in a low-temperature environment, comprising a porcelain insulation body, wherein the raw materials of the porcelain insulation body comprise: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; the porcelain insulator body prepared by the method of the invention has good strength and freeze-thaw aging resistance, so that the porcelain insulator can be used in occasions with large temperature changes and low-temperature environments such as high-altitude and high-latitude areas, and is not prone to low-temperature cracking and damage, thereby increasing the use range of the porcelain insulator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulator materials, in particular to an anti-aging porcelain insulator used in a low-temperature environment. Background Art

[0002] Porcelain insulators have been widely used in the power industry due to their excellent electromechanical properties, playing an important role in mechanical support and electrical insulation. During their service, porcelain insulators are subject to harsh operating environments, complex forces, and frequent fracture accidents, which seriously threaten the safe and stable operation of the power system. According to statistics of fracture accidents over the years, the probability of porcelain insulator fracture accidents is the highest in low-temperature winter environments. Therefore, optimizing the characteristics of porcelain insulators in low-temperature environments is of great significance to the reliable operation of porcelain insulators and the safety and stability of the system. Summary of the invention

[0003] To this end, the present invention provides an aging-resistant porcelain insulator for use in a low-temperature environment, comprising a porcelain insulating body, wherein the raw materials of the porcelain insulating body include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; the preparation method of the modified titanium dioxide powder is:

[0004] (1) in a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then the aqueous solution of urea is added to the solution under stirring. After the addition is completed, the temperature is kept constant at 50±5° C. in a water bath, and the solution is stirred for 5 to 6 minutes after the temperature is reached. Then, the ethanol solution of n-butyl titanate and polyethylene glycol is added to the solution under stirring. After the addition is completed, the temperature is kept constant at 50±5° C. for 5 to 6 minutes, and then the reaction kettle is sealed, and the temperature is raised to 120±3° C. and kept warm for more than 5 hours, and magnetic stirring is performed during the insulation process; after the insulation is completed, the reaction kettle is air-cooled to room temperature, the reaction kettle is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for more than 3 times, and dried at 60° C. for more than 30 minutes, and then placed in a muffle furnace at 550° C. and calcined for more than 6 hours to obtain titanium dioxide powder;

[0005] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, keeping the dispersion constant at 65±3° C. in a water bath, stirring the dispersion for 10 to 15 minutes, and then adding N-hydroxysuccinimide and L-lysine to the dispersion under stirring. After the addition is completed, keep the dispersion at 65±3° C. for more than 4 hours, then separate the solid and liquid, wash the solid phase with deionized water for more than 3 times, and dry at 60° C. for more than 30 minutes to obtain a pretreated powder;

[0006] (3) dispersing the pretreated powder in deionized water to form a suspension, and keeping the suspension in a water bath at a constant temperature of 35±3°C. After reaching the temperature, stirring the suspension for more than 5 minutes, and then adding dopamine to the suspension under stirring. After the addition is completed, stirring at a constant temperature of 35±3°C for more than 10 minutes, and then adding tris(hydroxymethyl)aminomethane to the suspension under stirring. After the addition is completed, stirring at a constant temperature of 35±3°C for more than 30 minutes, and then separating the solid and liquid, and drying the solid phase at 50°C for more than 8 hours to obtain a coated powder;

[0007] (4) In a nitrogen atmosphere, the coated powder is added to deionized water, stirred to form an aqueous suspension, the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the temperature is kept at 80±3° C. and stirred for more than 10 minutes, and then ammonium persulfate solution is added under stirring. After the addition is completed, the temperature is kept at 80±3° C. in a nitrogen atmosphere and stirred for more than 5 hours, and condensed and refluxed during the insulation process; after the insulation is completed, air-cooling to room temperature is performed, solid-liquid separation is performed, the solid phase is washed with deionized water for more than 3 times, and dried at 60° C. for more than 30 minutes to obtain the modified titanium dioxide powder.

[0008] Furthermore, the raw materials of the porcelain insulating body are calculated by weight as follows: 50 parts of mullite powder, 5-8 parts of potassium feldspar powder, 6-10 parts of zirconium oxide powder, 2-4 parts of barium carbonate powder, 14-16 parts of modified titanium dioxide powder, 2-4 parts of zinc oxide powder, 3-10 parts of magnesium oxide powder, and 20-30 parts of kaolin; each raw material is a fine powder passing through a 500-mesh sieve.

[0009] Furthermore, in the step (1), in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 6-8 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 20-25 g / L, the concentration of polyethylene glycol is 10-12 g / L, and the solvent is ethanol; in the aqueous solution of urea, the concentration of urea is 15-16 g / L; the added volume ratio of the aqueous solution of urea, n-butyl titanate, and the ethanol solution of polyethylene glycol to the volume ratio of the aqueous solution of hexadecyltrimethylammonium bromide is urea aqueous solution: n-butyl titanate, ethanol solution of polyethylene glycol: aqueous solution of hexadecyltrimethylammonium bromide = 1-2:10-15:20.

[0010] Furthermore, in the step (2), in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 4-6 g / 200 mL, and the solid-liquid mass ratio of the titanium dioxide powder dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is solid / liquid=1:100; the added mass ratio of the N-hydroxysuccinimide and L-lysine to the mass ratio of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2-3:4-7:1.

[0011] Furthermore, in the step (3), the solid-liquid mass ratio of the pretreated powder dispersed in deionized water to form a suspension is solid / liquid = 1:100; the mass ratio of the added mass of dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.6-0.8:0.1-0.2:1.

[0012] Furthermore, in the step (4), the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid=1:100; the mass percentage of ammonium persulfate in the ammonium persulfate solution is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropane sulfonic acid and the ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropane sulfonic acid: ammonium persulfate solution: coated powder=2-3:0.3-0.5:1.

[0013] The beneficial effect of the present invention is that the porcelain insulator body prepared by the method of the present invention has good strength and freeze-thaw aging resistance, so that the porcelain insulator can be used in occasions with large temperature changes and low-temperature environments such as high-altitude and high-latitude areas, and is not prone to low-temperature cracking and damage, thereby increasing the scope of use of the porcelain insulator. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the embodiments.

[0015] Example 1

[0016] An aging-resistant porcelain insulator for use in a low-temperature environment comprises a porcelain insulating body, the raw materials of which include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight as follows: 50 parts of mullite powder, 5 parts of potassium feldspar powder, 6 parts of zirconium oxide powder, 2 parts of barium carbonate powder, 14 parts of modified titanium dioxide powder, 2 parts of zinc oxide powder, 3 parts of magnesium oxide powder, and 20 parts of kaolin; each raw material is a fine powder that passes through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is as follows:

[0017] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 6 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 20 g / L, the concentration of polyethylene glycol is 10 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 15 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of cetyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of cetyltrimethylammonium bromide = 1:10:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0018] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 4 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added mass of the N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2:4:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0019] (3) The pretreated powder is dispersed in deionized water to form a suspension, wherein the pretreated powder is dispersed in deionized water to form a suspension in a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring. The mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.6:0.1:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder;

[0020] (4) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, wherein the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid = 1:100; the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the stirring is continued at 80±3° C. for 10 minutes, and then an ammonium persulfate solution is added under stirring, wherein the ammonium persulfate in the ammonium persulfate solution The mass percentage of the solvent is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: coated powder = 2:0.3:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5 hours, and condensation and reflux are carried out during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain the modified titanium dioxide powder.

[0021] Weigh each raw material according to the above weight proportion, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420℃ for pre-firing for 30min, then increase the temperature to 650℃ at 15℃ / min, keep warm for 30min, then increase the temperature to 1180℃ at 5℃ / min, and sinter for 3h; after sintering, cool down to 800℃ at 5℃ / min, keep warm for 10min, then cool down to 500℃ at 10℃ / min, keep warm for 10min, then cool down to 150℃ at 15℃ / min, take out and air cool to room temperature, and obtain a porcelain insulation body and a test sample.

[0022] Example 2

[0023] An aging-resistant porcelain insulator for use in a low-temperature environment comprises a porcelain insulating body, the raw materials of which include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight as follows: 50 parts of mullite powder, 6 parts of potassium feldspar powder, 8 parts of zirconium oxide powder, 3 parts of barium carbonate powder, 15 parts of modified titanium dioxide powder, 3 parts of zinc oxide powder, 5 parts of magnesium oxide powder, and 24 parts of kaolin; each raw material is a fine powder that passes through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is as follows:

[0024] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 7 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 22 g / L, the concentration of polyethylene glycol is 11 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 15 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 1:12:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0025] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 5 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2:5:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0026] (3) The pretreated powder is dispersed in deionized water to form a suspension, wherein the pretreated powder is dispersed in deionized water to form a suspension in a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring. The mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.7:0.1:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder;

[0027] (4) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, wherein the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid = 1:100; the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the stirring is continued at 80±3° C. for 10 minutes, and then an ammonium persulfate solution is added under stirring, wherein the ammonium persulfate in the ammonium persulfate solution The mass percentage of the solvent is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: coated powder = 2:0.4:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5 hours, and condensation and reflux are carried out during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain the modified titanium dioxide powder.

[0028] Weigh each raw material according to the above weight proportion, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420℃ for pre-firing for 30min, then increase the temperature to 650℃ at 15℃ / min, keep warm for 30min, then increase the temperature to 1180℃ at 5℃ / min, and sinter for 3h; after sintering, cool down to 800℃ at 5℃ / min, keep warm for 10min, then cool down to 500℃ at 10℃ / min, keep warm for 10min, then cool down to 150℃ at 15℃ / min, take out and air cool to room temperature, and obtain a porcelain insulation body and a test sample.

[0029] Example 3

[0030] An aging-resistant porcelain insulator for use in a low-temperature environment comprises a porcelain insulating body, the raw materials of which include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight as follows: 50 parts of mullite powder, 7 parts of potassium feldspar powder, 8 parts of zirconium oxide powder, 3 parts of barium carbonate powder, 15 parts of modified titanium dioxide powder, 3 parts of zinc oxide powder, 7 parts of magnesium oxide powder, and 26 parts of kaolin; each raw material is a fine powder that passes through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is as follows:

[0031] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 7 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 24 g / L, the concentration of polyethylene glycol is 11 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 16 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 2:14:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C for calcination for 6 hours to obtain titanium dioxide powder;

[0032] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 5 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added mass of the N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=3:6:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0033] (3) The pretreated powder is dispersed in deionized water to form a suspension, wherein the pretreated powder is dispersed in deionized water to form a suspension in a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring. The mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.7:0.2:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder;

[0034] (4) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, wherein the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid = 1:100; the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the stirring is continued at 80±3° C. for 10 minutes, and then an ammonium persulfate solution is added under stirring, wherein the ammonium persulfate in the ammonium persulfate solution The mass percentage of the solvent is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: coated powder = 3:0.4:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5 hours, and condensation and reflux are carried out during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain the modified titanium dioxide powder.

[0035] Weigh each raw material according to the above weight proportion, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420℃ for pre-firing for 30min, then increase the temperature to 650℃ at 15℃ / min, keep warm for 30min, then increase the temperature to 1180℃ at 5℃ / min, and sinter for 3h; after sintering, cool down to 800℃ at 5℃ / min, keep warm for 10min, then cool down to 500℃ at 10℃ / min, keep warm for 10min, then cool down to 150℃ at 15℃ / min, take out and air cool to room temperature, and obtain a porcelain insulation body and a test sample.

[0036] Example 4

[0037] An aging-resistant porcelain insulator for use in a low-temperature environment comprises a porcelain insulating body, the raw materials of which include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight as follows: 50 parts of mullite powder, 8 parts of potassium feldspar powder, 10 parts of zirconium oxide powder, 4 parts of barium carbonate powder, 16 parts of modified titanium dioxide powder, 4 parts of zinc oxide powder, 10 parts of magnesium oxide powder, and 30 parts of kaolin; each raw material is a fine powder that passes through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is as follows:

[0038] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 8 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 25 g / L, the concentration of polyethylene glycol is 12 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 16 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 2:15:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0039] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 6 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added mass of the N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=3:7:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0040] (3) The pretreated powder is dispersed in deionized water to form a suspension, wherein the pretreated powder is dispersed in deionized water to form a suspension in a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring. The mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.8:0.2:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder;

[0041] (4) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, wherein the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid = 1:100; the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the stirring is continued at 80±3° C. for 10 minutes, and then an ammonium persulfate solution is added under stirring, wherein the ammonium persulfate in the ammonium persulfate solution The mass percentage of the solvent is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: coated powder = 3:0.5:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5 hours, and condensation and reflux are carried out during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain the modified titanium dioxide powder.

[0042] Weigh each raw material according to the above weight proportion, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420℃ for pre-firing for 30min, then increase the temperature to 650℃ at 15℃ / min, keep warm for 30min, then increase the temperature to 1180℃ at 5℃ / min, and sinter for 3h; after sintering, cool down to 800℃ at 5℃ / min, keep warm for 10min, then cool down to 500℃ at 10℃ / min, keep warm for 10min, then cool down to 150℃ at 15℃ / min, take out and air cool to room temperature, and obtain a porcelain insulation body and a test sample.

[0043] Comparative Example 1

[0044] A porcelain insulating body for comparison, the raw materials of the porcelain insulating body include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight: 50 parts of mullite powder, 6 parts of potassium feldspar powder, 8 parts of zirconium oxide powder, 3 parts of barium carbonate powder, 15 parts of modified titanium dioxide powder, 3 parts of zinc oxide powder, 5 parts of magnesium oxide powder, 24 parts of kaolin; each raw material is a fine powder passing through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is:

[0045] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 7 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 22 g / L, the concentration of polyethylene glycol is 11 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 15 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 1:12:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0046] (2) dispersing the titanium dioxide powder in deionized water to form a suspension, wherein the titanium dioxide powder is dispersed in deionized water to form a suspension in a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring. The mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the titanium dioxide powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:titanium dioxide powder = 0.7:0.1:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder;

[0047] (3) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, wherein the coated powder is added to the deionized water in a solid-liquid mass ratio of 1:100; the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the temperature is kept at 80±3° C. and stirred for 10 minutes, and then ammonium persulfate solution is added under stirring, and the mass ratio of ammonium persulfate in the ammonium persulfate solution is The amount percentage is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: coated powder = 2:0.4:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5h, and condensation and reflux are performed during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30min to obtain the modified titanium dioxide powder described in this comparative example.

[0048] Weigh each raw material according to the above weight proportions, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420°C for pre-firing for 30min, then increase the temperature to 650°C at 15°C / min, keep warm for 30min, then increase the temperature to 1180°C at 5°C / min, and sinter for 3h; after sintering, cool to 800°C at 5°C / min, keep warm for 10min, then cool to 500°C at 10°C / min, keep warm for 10min, then cool to 150°C at 15°C / min, take out and air cool to room temperature, and obtain the porcelain insulation body and test sample of this comparative example.

[0049] Comparative Example 2

[0050] A porcelain insulating body for comparison, the raw materials of the porcelain insulating body include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight: 50 parts of mullite powder, 6 parts of potassium feldspar powder, 8 parts of zirconium oxide powder, 3 parts of barium carbonate powder, 15 parts of modified titanium dioxide powder, 3 parts of zinc oxide powder, 5 parts of magnesium oxide powder, 24 parts of kaolin; each raw material is a fine powder passing through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is:

[0051] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 7 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 22 g / L, the concentration of polyethylene glycol is 11 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 15 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 1:12:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0052] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 5 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2:5:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0053] (3) In a nitrogen atmosphere, the pretreated powder is added to deionized water and stirred to form an aqueous suspension, wherein the solid-liquid mass ratio of the pretreated powder added to the deionized water is solid / liquid = 1:100; the aqueous suspension is kept constant at 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the stirring is continued at 80±3° C. for 10 minutes, and then, ammonium persulfate solution is added under stirring, and the mass ratio of ammonium persulfate in the ammonium persulfate solution is The amount percentage is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropanesulfonic acid and ammonium persulfate solution to the pretreated powder in the water suspension is 2-acrylamide-2-methylpropanesulfonic acid: ammonium persulfate solution: pretreated powder = 2:0.4:1; after the addition is completed, the mixture is kept warm and stirred at 80±3°C in a nitrogen atmosphere for 5h, and condensation and reflux are carried out during the insulation process; after the insulation is completed, the mixture is air-cooled to room temperature, the solid-liquid separation is performed, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30min to obtain the modified titanium dioxide powder described in this comparative example.

[0054] Weigh each raw material according to the above weight proportions, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420°C for pre-firing for 30min, then increase the temperature to 650°C at 15°C / min, keep warm for 30min, then increase the temperature to 1180°C at 5°C / min, and sinter for 3h; after sintering, cool to 800°C at 5°C / min, keep warm for 10min, then cool to 500°C at 10°C / min, keep warm for 10min, then cool to 150°C at 15°C / min, take out and air cool to room temperature, and obtain the porcelain insulation body and test sample of this comparative example.

[0055] Comparative Example 3

[0056] A porcelain insulating body for comparison, the raw materials of the porcelain insulating body include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight: 50 parts of mullite powder, 6 parts of potassium feldspar powder, 8 parts of zirconium oxide powder, 3 parts of barium carbonate powder, 15 parts of modified titanium dioxide powder, 3 parts of zinc oxide powder, 5 parts of magnesium oxide powder, 24 parts of kaolin; each raw material is a fine powder passing through a 500-mesh sieve. The preparation method of the modified titanium dioxide powder is:

[0057] (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 7 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 22 g / L, the concentration of polyethylene glycol is 11 g / L, and the solvent is ethanol; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then an aqueous solution of urea is added to the solution under stirring, and the concentration of urea in the aqueous solution of urea is 15 g / L; after the addition is completed, the water bath is kept at a constant temperature of 50±5°C, the solution is stirred for 5 minutes after reaching the temperature, and then the solution is added to the solution under stirring. Add the ethanol solution of n-butyl titanate and polyethylene glycol, the added volume ratio of the aqueous solution of urea, n-butyl titanate and the ethanol solution of polyethylene glycol to the aqueous solution of hexadecyltrimethylammonium bromide is the aqueous solution of urea: the ethanol solution of n-butyl titanate and polyethylene glycol: the aqueous solution of hexadecyltrimethylammonium bromide = 1:12:20; after the addition is completed, continue to stir at a constant temperature of 50±5°C for 5 minutes, then seal the reactor, heat to 120±3°C and keep warm for 5 hours, and stir magnetically during the insulation process; after the insulation is completed, air cool to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, dry at 60°C for 30 minutes, and then place it in a muffle furnace at 550°C and calcine for 6 hours to obtain titanium dioxide powder;

[0058] (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, wherein the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the aqueous solution is 5 g / 200 mL, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, wherein the titanium dioxide powder is dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. The solid-liquid mass ratio is solid / liquid=1:100; the dispersion is kept at a constant temperature of 65±3°C in a water bath, and then the dispersion is stirred for 10 minutes, and then N-hydroxysuccinimide and L-lysine are added to the dispersion under stirring, and the mass ratio of the added N-hydroxysuccinimide and L-lysine to the mass of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2:5:1; after the addition is completed, the temperature is kept at 65±3°C for 4 hours, and then the solid-liquid is separated, the solid phase is washed 3 times with deionized water, and dried at 60°C for 30 minutes to obtain a pretreated powder;

[0059] (3) The pretreated powder is dispersed in deionized water to form a suspension, wherein the pretreated powder is dispersed in deionized water to form a suspension with a solid-liquid mass ratio of solid / liquid = 1:100; the suspension is kept at a constant temperature of 35±3°C in a water bath, and the suspension is stirred for 5 minutes after reaching the temperature, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 10 minutes, and then tris(hydroxymethyl)aminomethane is added to the suspension under stirring, and the mass ratio of the added dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.7:0.1:1; after the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for 30 minutes, and then the solid and liquid are separated, and the solid phase is dried at 50°C for 8 hours to obtain a coated powder as the modified titanium dioxide powder described in this comparative example.

[0060] Weigh each raw material according to the above weight proportions, mix each raw material evenly to form a mixed powder, then add water to adjust the water content to 25wt%, press into a blank, heat to 420°C for pre-firing for 30min, then increase the temperature to 650°C at 15°C / min, keep warm for 30min, then increase the temperature to 1180°C at 5°C / min, and sinter for 3h; after sintering, cool to 800°C at 5°C / min, keep warm for 10min, then cool to 500°C at 10°C / min, keep warm for 10min, then cool to 150°C at 15°C / min, take out and air cool to room temperature, and obtain the porcelain insulation body and test sample of this comparative example.

[0061] Example 5

[0062] The tensile strength and freeze-thaw aging resistance of the test samples prepared by the methods described in the above embodiments and comparative examples were tested. The tensile strength was tested on a tensile machine, and the test parameters of each sample were exactly the same. The freeze-thaw aging resistance was tested by repeatedly freezing and thawing the sample at -50 to 40 ° C for 60 times, and observing whether cracks were generated on the surface of the sample. The results are shown in Table 1.

[0063] Table 1

[0064] Experimental Group Tensile strength / MPa Freeze-thaw resistance Example 1 279 No cracks on the surface Example 2 291 No cracks on the surface Example 3 286 No cracks on the surface Example 4 281 No cracks on the surface Comparative Example 1 232 A few cracks on the surface Comparative Example 2 218 A few cracks on the surface Comparative Example 3 224 A few cracks on the surface

[0065] As shown in Table 1, the porcelain insulator body prepared by the method of the present invention has good strength and freeze-thaw aging resistance, so that the porcelain insulator can be used in occasions with large temperature changes, as well as low-temperature environments such as high-altitude and high-latitude areas, and is not prone to low-temperature cracking and damage, thereby increasing the scope of use of the porcelain insulator. Comparative Example 2 and the comparative examples show that the mechanical properties of the insulator obtained by adding the powder treated by the modification process of the present invention are significantly improved compared to the powder that is not completely modified. It can be seen that the modification process has a huge impact on the performance of the porcelain insulator, which may be mainly related to the modification process affecting the particle distribution dispersion and the bonding strength between particles.

[0066] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. An anti-aging porcelain insulator for use in a low temperature environment, characterized in that: The invention comprises a porcelain insulating body, wherein the raw materials of the porcelain insulating body include: mullite powder, potassium feldspar powder, zirconium oxide powder, barium carbonate powder, modified titanium dioxide powder, zinc oxide powder, magnesium oxide powder and kaolin; each raw material is calculated by weight as follows: 50 parts of mullite powder, 5-8 parts of potassium feldspar powder, 6-10 parts of zirconium oxide powder, 2-4 parts of barium carbonate powder, 14-16 parts of modified titanium dioxide powder, 2-4 parts of zinc oxide powder, 3-10 parts of magnesium oxide powder and 20-30 parts of kaolin; each raw material is a fine powder passing through a 500-mesh sieve; the preparation method of the modified titanium dioxide powder is as follows: (1) In a reaction kettle, an aqueous solution of hexadecyltrimethylammonium bromide and an ethanol solution of n-butyl titanate and polyethylene glycol are prepared; the aqueous solution of hexadecyltrimethylammonium bromide is stirred, and then the aqueous solution of urea is added to the solution under stirring. After the addition is completed, the temperature is kept constant at 50±5° C. in a water bath, and the solution is continuously stirred for 5 to 6 minutes after the temperature is reached. Then, the ethanol solution of n-butyl titanate and polyethylene glycol is added to the solution under stirring. After the addition is completed, the temperature is kept constant at 50±5° C. and stirred for 5 to 6 minutes. Then, the reaction kettle is sealed, and the temperature is raised to 120±3° C. and kept warm for more than 5 hours, with magnetic stirring during the insulation process. After the insulation is completed, the reaction kettle is air-cooled to room temperature, the reaction kettle is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for more than 3 times, and dried at 60° C. for more than 30 minutes, and then placed in a muffle furnace at 550° C. and calcined for more than 6 hours to obtain titanium dioxide powder; (2) preparing an aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, dispersing the titanium dioxide powder in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to form a dispersion, keeping the dispersion constant at 65±3° C. in a water bath, stirring the dispersion for 10 to 15 minutes, and then adding N-hydroxysuccinimide and L-lysine to the dispersion under stirring. After the addition is completed, the dispersion is kept at 65±3° C. for more than 4 hours, followed by solid-liquid separation, washing the solid phase with deionized water for more than 3 times, and drying at 60° C. for more than 30 minutes to obtain a pretreated powder; (3) The pretreated powder is dispersed in deionized water to form a suspension, and the suspension is kept at a constant temperature of 35±3°C in a water bath. After reaching the temperature, the suspension is stirred for more than 5 minutes, and then dopamine is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for more than 10 minutes. Then, tris(hydroxymethyl)aminomethane is added to the suspension under stirring. After the addition is completed, the suspension is stirred at a constant temperature of 35±3°C for more than 30 minutes. Then, the solid-liquid separation is performed, and the solid phase is dried at 50°C for more than 8 hours to obtain a coated powder; (4) In a nitrogen atmosphere, the coated powder is added to deionized water and stirred to form an aqueous suspension, the aqueous suspension is kept at a constant temperature of 80±3° C. in a water bath, and condensed and refluxed; then, 2-acrylamide-2-methylpropanesulfonic acid is added to the aqueous suspension under stirring in a nitrogen atmosphere, and after the addition is completed, the temperature is kept at 80±3° C. and stirred for more than 10 minutes, and then ammonium persulfate solution is added under stirring. After the addition is completed, the temperature is kept at 80±3° C. in a nitrogen atmosphere and stirred for more than 5 hours, and condensed and refluxed during the insulation process; after the insulation is completed, air-cooling is performed to room temperature, solid-liquid separation is performed, the solid phase is washed with deionized water for more than 3 times, and dried at 60° C. for more than 30 minutes to obtain the modified titanium dioxide powder.

2. The anti-aging porcelain insulator for use in a low temperature environment according to claim 1, characterized in that: In the step (1), in the aqueous solution of hexadecyltrimethylammonium bromide, the concentration of hexadecyltrimethylammonium bromide is 6-8 g / L, and the solvent is water; in the ethanol solution of n-butyl titanate and polyethylene glycol, the concentration of n-butyl titanate is 20-25 g / L, the concentration of polyethylene glycol is 10-12 g / L, and the solvent is ethanol; in the aqueous solution of urea, the concentration of urea is 15-16 g / L; the added volume ratio of the aqueous solution of urea, n-butyl titanate, and the ethanol solution of polyethylene glycol to the volume ratio of the aqueous solution of hexadecyltrimethylammonium bromide is urea aqueous solution: n-butyl titanate, ethanol solution of polyethylene glycol: aqueous solution of hexadecyltrimethylammonium bromide = 1-2:10-15:

20.

3. The anti-aging porcelain insulator for use in a low temperature environment according to claim 1, characterized in that: In the step (2), in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 4-6 g / 200 mL, and the solid-liquid mass ratio of the titanium dioxide powder dispersed in the aqueous solution of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is solid / liquid=1:100; the added mass ratio of the N-hydroxysuccinimide and L-lysine to the mass ratio of the titanium dioxide powder in the dispersion is N-hydroxysuccinimide:L-lysine:titanium dioxide powder=2-3:4-7:

1.

4. The anti-aging porcelain insulator for use in a low temperature environment according to claim 1, characterized in that: In the step (3), the solid-liquid mass ratio of the pretreated powder dispersed in deionized water to form a suspension is solid / liquid = 1:100; the mass ratio of the added mass of dopamine and tris(hydroxymethyl)aminomethane to the mass of the pretreated powder in the suspension is dopamine:tris(hydroxymethyl)aminomethane:pretreated powder = 0.6-0.8:0.1-0.2:

1.

5. The anti-aging porcelain insulator for use in low temperature environment according to claim 1, characterized in that: In the step (4), the solid-liquid mass ratio of the coated powder added to the deionized water is solid / liquid=1:100; the mass percentage of ammonium persulfate in the ammonium persulfate solution is 3%, and the solvent is water; the mass ratio of the added mass of the 2-acrylamide-2-methylpropane sulfonic acid and the ammonium persulfate solution to the coated powder in the water suspension is 2-acrylamide-2-methylpropane sulfonic acid: ammonium persulfate solution: coated powder=2-3:0.3-0.5:1.

Citation Information

Patent Citations

  • High-strength and shock-resistant porcelain insulator and preparation method thereof

    CN108840660A

  • High-strength porcelain insulator and preparation method thereof

    CN110467442A